2018
DOI: 10.1186/s12873-018-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of injury in patients visiting the emergency Department of Yirgalem General Hospital, Southern Ethiopia

Abstract: BackgroundTraumatic injuries continue to be an important cause of morbidity and mortality in the developing world. Despite the high burden of injury in Ethiopia, the occurrence and health impact have not received due attention. The aim of the study was to assess the prevalence and outcome of injury among patients visiting the Emergency Department (ED) of Yirgalem General Hospital, southern Ethiopia.MethodsA facility-based prospective cross sectional study was conducted from March, 27 – April, 30/2017. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 4 publications
6
34
2
Order By: Relevance
“…The majority of the patients were primary school attendants and students. This finding is in line with the study conducted in Yirgalem, Nigeria, and Tanzania (2,23,24). A multicenter study conducted in Amhara Regional State found that the illiterate and farmers were the most likely injured patients unlike the findings of this study (6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the patients were primary school attendants and students. This finding is in line with the study conducted in Yirgalem, Nigeria, and Tanzania (2,23,24). A multicenter study conducted in Amhara Regional State found that the illiterate and farmers were the most likely injured patients unlike the findings of this study (6).…”
Section: Discussionsupporting
confidence: 92%
“…Injury has become a life-threatening community health problem associated with significant mortality and morbidity worldwide (1,2,(11)(12)(13)(14)(15)(16)(17)(18)(3)(4)(5)(6)(7)(8)(9)(10). According to the World Health Organization (WHO) injury and violence surveillance, more than 5 million people die per year due to injury which accounts for 9% of the world's deaths (19).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, patients from rural area are more affected with injury as compared to urban and this finding is consistent with a study done in University of Gondar and Yirgalem 2,7 . However, patients residing in Urban are affected more likely as compared to patients from rural in multicenter study conducted in Amhara regional state and Sub-Saharan African countries 6,20 .…”
Section: Discussionsupporting
confidence: 92%
“…The majority of patients were primary School attendants and student in regard to occupational status. This finding is comparable with a study conducted in Yirgalem, Nigeria and Tanzania 2,23,24 . A multicenter study conducted in Amhara regional state found that illiterate and Farmer were the most likely injured patients in contrary to this study finding 6 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation